Do Red Herrings Swim in Circles? – Controlling for the Endogeneity of Time to Death - Stefan Felder; Andreas Werblow; Peter Zweifel (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
Studies on the effect of ageing on health care expenditures (HCE) have revealed the importance of controlling for time-to-death (TTD). These studies, however, are subject to possible endogeneity if HCE influences remaining life expectancy. This paper introduces a ten year observational period on monthly HCE, socioeconomic characteristics, and survivor status to first predict TTD and then uses predicted values of TTD as an instrument in the regression for HCE. While exogeneity of TTD has to be rejected, core results concerning the role of TTD rather than age as a determinant of HCE (the red herring hypothesis) are confirmed.
Keywords: I10; D12; 330; Health care expenditure; proximity to death; ageing; red herring hypothesis; Gesundheitskosten; Alternde Bevölkerung; Sterblichkeit; Schätzung; Deutschland